Legal Criticism Of The Code Of Law The New Criminal Law Is Viewed From The Point Of View Philosophical, Sociological And Juridical - Soedirjo, Achmad Taufan; Jaya, Surya (International Journal Labs, 2023)
The need for a new National Criminal Code is based on philosophical, sociological, and legal considerations, among others: